Prevalence of psychoactive substance use among acutely hospitalised patients in Oslo and Moscow: a cross-sectional, observational study - Gamboa, Danil (BMJ Open, 2020)
OBJECTIVES: The use of psychoactive prescription medication is increasing in the general population. This is a cause for concern, particularly among the elderly, where physiological changes related to senescence increase the risk for adverse effects. While previous studies regarding psychoactive substance use have generally been population based, we sought to determine the frequency of such use among acutely hospitalised patients. SETTING: Two emergency departments (EDs), one in Oslo and one in Moscow, admitting patients to Departments of Internal Medicine. PARTICIPANTS: 5583 patients aged ≥18 years participated, distributed evenly between genders and study locations. Patients unable to give informed consent were excluded. The study sites did not admit patients with surgical conditions and/or injuries. PRIMARY AND SECONDARY OUTCOMES: The presence of psychoactive substances was determined through blood analysis using liquid chromatography-mass spectrometry. Secondary outcomes comprised demographic data (including age, gender, employment and marital status), degree of psychological distress, concurrent alcohol use, and self-reported alcohol, psychoactive drug and illicit substance use. RESULTS: 32.3% in Oslo and 12% in Moscow were positive for one or more psychoactive medicinal drugs (benzodiazepines, z-hypnotics, opioids or barbiturates). In Oslo, medicinal drug use was associated with being aged 61 to 70 years (OR 2.40, 95% CI 1.61 to 3.58) compared with 18 to 40 years, and psychological distress (OR 2.61, 95% CI 2.06 to 3.30). In Moscow, psychoactive medicinal drug use was also associated with psychological distress (OR 1.68, 95% CI 1.18 to 2.39), and was less common among patients aged 41 to 60 years (OR 0.62, 95% CI 0.43 to 0.88) than among patients aged 18 to 40 years. CONCLUSION: A significant proportion of admitted patients used one or more psychoactive medicinal drugs, in particular benzodiazepines (Oslo and Moscow) and opiates (Oslo). We suggest formalised screening for inappropriate prescription drug use and increased adherence to clinical prescription guidelines.